Internalisasi Nilai-Nilai Pendidikan Anti Kekerasan Melalui Pembelajaran PAI di SDN Pademawu Barat 2 Pamekasan - Maufiroh, Holidatul; Sa'i, Mad (Journal of Teacher Training and Educational Research, 2024)
The internalization of anti-violence education values through Islamic Education (PAI) learning is a process of instilling mental attitudes that prioritize positive, anti-violence values when facing any social-religious problems through PAI learning. This paper aims to identify and describe the internalization of anti-violence education values through PAI learning. The research method used in this article is qualitative research with a descriptive approach. The results and discussion in this paper indicate that the internalization process is carried out by strengthening each student through religious culture and PAI subjects, which reduces violence in the educational environment and enhances students' faith and piety through the conscious internalization of religious values implemented by the school